Penurunan Tarif Pph, Penerapan E-Registration, E-Filing, E-Billing dan Sosialisasi Perpajakan Terhadap Kepatuhan Wajib Pajak Umkm pada KPP Krembangan Surabaya - Dinar Gusti Nabilah; Munari Munari (IPM2KPE, 2023)
This research aims to empirically test and prove the effect of reducing income tax rates, implementing e-registration, e-filing, e-billing, and tax socialization on MSME taxpayer compliance at the Krembangan Surabaya KPP. The research method used is quantitative with the type of data used is primary data. The research results show that the reduction in income tax rates has a positive and insignificant effect, the implementation of e-registration has a positive and significant effect, the implementation of e-filing has a positive and significant effect, the implementation of e-billing has a positive and significant effect, and the socialization of taxation has a positive and insignificant effect. The conclusion is that the technology applied in the taxation system has a significant impact on taxpayer compliance. Keywords: Reducing Income Tax Rates, E-Registration, E-Filing, E-Billing, Taxation